The Characteristics and Perspectives of HIV-Positive Individuals among the Key and Vulnerable Populations in Surabaya, Indonesia - Wienta Diarsvitri; Retno Budiarti; Olivia Mahardani Adam; I Ketut Tirka Nandaka; Herjunianto Herjunianto; Carlo Micelli; Vincentius Edwin Pradana Setiawan; Ade Putera Angkiriwang; Ciendracianto Gandhatama; Cindy Angelina Limantara; Firyal Ilona; Quri Meihaerani Savitri; Darren Tjiasmanto; Florencia Christina Sindhu (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2026)
There is an ongoing challenge of promoting HIV testing uptake and sustained treatment adherence among key and vulnerable populations. This study aimed to determine the characteristics and perspectives of HIV-positive individuals among the key and vulnerable populations in Surabaya, Indonesia. This was a cross-sectional study with a mixed-methods in HIV-positive key and vulnerable populations. Clinical and laboratory data were obtained from medical records. A questionnaire collected data on sociodemographic characteristics, behavior, sexual practices, cognitive function, depression, and quality of life. The study indicated that 52.8% of participants were HIV-late diagnosis with several characteristics: being male (p=0.021); having lower BMI (p=0.001), lower lymphocyte count (p<0.001), poor knowledge of HIV cause (p=0.016), low quality of life on physical health (p<0.001), psychological health (p=0.020), and social relationship (p<0.001); lower cognitive function (p<0.001); and moderate to severe depression (p<0.001) than non-HIV late diagnosis. The interviews revealed that most participants hid their HIV status from their families and experienced stigma. NGO staff played a crucial role in educating, encouraging, and assisting them in accessing relevant health services. More than half of the participants were diagnosed late. Improving community-based programs, expanding mental health resources, and reducing stigma are the key strategies for enhancing HIV-related outcomes.